Curating live arts critical perspectives, essays, and conversations on theory and practice - Davida, Dena; Pronovost, Marc; Hudon, Véronique; Jane Gabriels (Berghahn Books, 2019)
Situated at the crossroads of performance practice, museology, and cultural studies, live arts curation has grown in recent years to become a vibrant interdisciplinary project and a genuine global phenomenon.